IMPLEMENTATION OF SCIENCE LEARNING THROUGH EXPERIMENTAL METHODS OF MIXING COLORS IN EARLY CHILDHOOD AT TK NEGERI 4 BOKAN ISLANDS TOROPOT VILLAGE - Zahra, Afifah; Safitri, Riskal; Nasaruddin, Nasaruddin (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This qualitative research focused on how science learning was implemented through color-mixing experiments for early childhood students. Data collection techniques included observations, interviews, and documentation, analyzed through data collection, data presentation, and conclusion drawing. The study revealed that 7 students demonstrated progress categorized as "starting to develop," and 5 students were "developing as expected." For the indicator of naming colors, 1 student was "starting to develop," and 11 students were "developing as expected." Regarding the ability to differentiate colors, 6 students were categorized as "starting to develop," and 6 students were "developing as expected." For the indicator of pointing to colors, 8 students reached the "developing as expected" level, and 4 students achieved the "very well developed" category. In the advanced results for naming colors, 2 students were "developing as expected," while 10 students achieved the "very well developed" category. Similarly, for the ability to differentiate colors, 6 students were "developing as expected," and 6 students were "very well developed."